2018
DOI: 10.47657/2018201353
|View full text |Cite
|
Sign up to set email alerts
|

The impact of academic libraries on students' academic achievement: The relationship between learning styles and information seeking anxiety

Abstract: Information seeking anxiety is a type of anxiety that affects academic performance. The present study was aimed at investigating the relationship between learning styles and information seeking anxiety in relation to the academic achievement of students. This was a descriptive-analytic research, and the study population consisted of students who had passed at least one semester in Behbahan University, Iran. The sample size was calculated 181 from the Morgan table. The results of this study showed that most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The study of Rahimi and Bayat (2015) discovered an inverse relationship between English language proficiency and ISA. An inquiry by Parvin et al (2019) also discovered no correlation between students’ learning style and ISA. Akbarzadeh et al (2020) reported that the thinking styles such as local thinking style, conservative thinking style and monarchic thinking style as a positive predictor of ISA, whereas the judiciary thinking style negatively predicted ISA.…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…The study of Rahimi and Bayat (2015) discovered an inverse relationship between English language proficiency and ISA. An inquiry by Parvin et al (2019) also discovered no correlation between students’ learning style and ISA. Akbarzadeh et al (2020) reported that the thinking styles such as local thinking style, conservative thinking style and monarchic thinking style as a positive predictor of ISA, whereas the judiciary thinking style negatively predicted ISA.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Business students constituted a significant group in different universities which needed to be prepared as an independent, confident, self-directed and information literate learners equipped with lifelong learning capabilities so that they might be able to make informed decisions to achieve a competitive advantage in the workplace (Naveed and Mahmood, 2019). These students needed to navigate with the digital information landscape confidently rather than anxiously during the process of information seeking for a sustainable performance not only in academia but also in the workplace (Khan et al , 2021; Parvin et al , 2019). Some studies reported that information-related anxieties have a negative effect on information seeking among university students, which ultimately affect their academic performance (Hadavi and Farhadpoor, 2020, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%